The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1093/humrep/dep024
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dietary patterns and semen quality in men undergoing IVF/ICSI treatment

Abstract: BACKGROUND This study investigates whether dietary patterns, substantiated by biomarkers, are associated with semen quality. METHODS In 161 men of subfertile couples undergoing in vitro fertilization treatment in a tertiary referral clinic in Rotterdam, the Netherlands, we assessed nutrient intakes and performed principal component factor analysis to identify dietary patterns. Total homocysteine (tHcy), folate, vitamin B12 and B6 were measured in blood and seminal plasma. Semen quality was assessed by sperm vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
158
7
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(173 citation statements)
references
References 28 publications
5
158
7
3
Order By: Relevance
“…The findings presented here are not entirely consistent with a similar study performed among subfertile men attending an in vitro fertilization clinic in the Netherlands (Vujkovic et al, 2009). In the latter study, the authors found a positive association between adherence to a 'Traditional Dutch' diet and sperm concentration and an inverse association between adherence to a 'Health Conscious' diet and DNA fragmentation index.…”
Section: Discussioncontrasting
confidence: 95%
“…The findings presented here are not entirely consistent with a similar study performed among subfertile men attending an in vitro fertilization clinic in the Netherlands (Vujkovic et al, 2009). In the latter study, the authors found a positive association between adherence to a 'Traditional Dutch' diet and sperm concentration and an inverse association between adherence to a 'Health Conscious' diet and DNA fragmentation index.…”
Section: Discussioncontrasting
confidence: 95%
“…A study in Spain found that intake of processed red meats was ;31% higher among oligoasthenoteratospermic men than among controls but did not find any difference in fish intake between cases and controls (13). Another study in the Netherlands found that fish and other seafood was associated with higher sperm motility (14). A third study among subfertile men in Iran found that the odds of asthenospermia was higher among men consuming the highest amounts of processed red meat compared with those consuming the lowest amounts, but lower among men in the highest tertile of fish and other seafood intake compared with those in the first tertile of intake (16).…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature on the relation between meat intake and semen quality indicators is scarce and limited to crosssectional and case-control studies (13)(14)(15)(16)(17). We have previously reported that processed meat intake is associated with lower total sperm count among physically active healthy young men (17).…”
Section: Introductionmentioning
confidence: 99%
“…2 One of the reasons for the impaired semen parameters over the years is dietary factors. 3,4 The significant effects of dietary fatty acids (FAs) on male fertility have been well documented both in animal and human studies. 5,6 There are three types of natural FAs: saturated, monounsaturated and polyunsaturated.…”
mentioning
confidence: 99%